Geospatial simulation steering for adaptive management. (November 2020) - Petrasova, Anna; Gaydos, Devon A.; Petras, Vaclav; Jones, Chris M.; Mitasova, Helena; Meentemeyer, Ross K.
Abstract: Spatio-temporal simulations are becoming essential tools for decision makers when forecasting future conditions and evaluating effectiveness of alternative decision scenarios. However, lack of interactive steering capabilities limits the value of advanced stochastic simulations for research and practice. To address this gap we identified conceptual challenges associated with steering stochastic, spatio-temporal simulations and developed solutions that better represent the realities of decision-making by allowing both reactive and proactive, spatially-explicit interventions. We present our approach, in a participatory modeling case study engaging stakeholders in developing strategies to contain the spread of a tree disease in Oregon, USA. Using intuitive interfaces, implemented through web-based and tangible platforms, stakeholders explored management options as the simulation progressed. Spatio-temporal steering allowed them to combine currently used management practices into novel adaptive management strategies, which were previously difficult to test and assess, demonstrating the utility of interactive simulations for decision-making. Graphical abstract: Image 1 Highlights: Computational steering of stochastic geospatial simulations poses unique challenges. Steering geospatial simulations enables exploring adaptive management scenarios. With intuitive interfaces steering can be successfully used in participatory modeling.